Structural and Luminescence Properties of Sm3+ Doped TTB -Type BaTa2O6 Ceramic Phosphors - BAŞAK, ALİ SADİ; EKMEKÇİ, METE KAAN; DENİZ, SABAHATTİN (SPRINGER/PLENUM PUBLISHERS, 2015)
Pure and 0.5 to 10 mole% Sm3+ doped TTB (tetragonal tungsten bronze)-type BaTa2O6 ceramic phosphor was produced by the solid state reaction method which performed at 1425 A degrees C for 20 h. XRD and SEM analysis indicated single TTB phase for undoped and 0.5 to 10 mole% Sm3+ doped BaTa2O6 structures. SEM also showed that the BaTa2O6 grain size decreased with the increasing content of Sm3+. Optical analysis indicated significant emissions in the visible spectral region as green (lambda = 562.7 nm) and orange-reddish (lambda = 597.1 nm). The emission intensity increased with the increasing doping concentration up to 2.5 mole%, and then decreased due to the concentration quenching effect.
Keywords: TTB-type BaTa2O6; Photoluminescence; Solid state reaction; CRYSTAL-CHEMISTRY; PHASE